The Successful Merchant and his Ethics in Islam - Shuhaib; Isman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Trade is of great importance, and Islam has recommended it, magnified its importance, and praised its pious people who are upright and keep what God has obligated and stay away from what God forbids, and trade is one of the most important works of Muslims and one of the most important ways of earning money. There is no doubt that trade is one of the best worldly works in which people work to collect their livelihoods and the livelihoods of their families and dependents, and serve their communities, and what distinguishes a Muslim trader from others: His adherence to the values of his religion and his constant reliance on his Lord. Therefore, it was imperative for every Muslim merchant at this time to familiarize himself with the ethics, do's and don'ts that relate to his business; this is because of the spread of prohibitions and the many suspicions that affect most transactions, deviating them from the legitimate controls that Allah Almighty has commanded. For all these reasons, the researcher believes in mentioning some ethics in trade that must be practiced by the merchant in his transactions in order to obtain the blessing of money and avoid things that destroy its blessing.